Spatiotemporal dynamics of microcystin contamination in fish across the Lake Chaohu basin under the Yangtze River ten-year fishing ban: Ecological and human health implications - Shengpan Han; Wulai Xia; Jun He; Qianhui Wu; Wenli Xu; Jia Yu; Jun Chen; Ping Xie (Ecotoxicology and Environmental Safety)
Microcystins (MCs), produced by harmful cyanobacterial blooms, pose a threat to aquatic ecosystems and public health in the Yangtze River basin, including Lake Chaohu, which implemented a ten-year fishing ban in 2021 for ecological restoration. This study provides the first basin-wide assessment of MC contamination in fish muscle tissues from Lake Chaohu and its major tributaries during the ban's initial phase (2022–2023), with comparisons to pre-ban data. Using UHPLC-MS/MS, we quantified MC-LR and MC-RR in fish from four trophic levels (planktivorous, omnivorous, herbivorous, and carnivorous). Results revealed that MC-RR was the predominant variant, and planktivorous fish exhibited the highest MC levels, followed by omnivorous, herbivorous, and carnivorous species, reflecting dynamics of trophic transfer. Overall, fish MC concentrations were significantly lower during the ban compared to pre-ban levels, demonstrating positive initial effects. Seasonal analysis revealed higher MC levels in warmer seasons, but detectable MCs persisted during cold seasons, reflecting ongoing contamination. Spatially, while fish in the lake exhibited higher MC concentrations, contamination was also detected in riverine fish, highlighting the basin-wide spread. Despite a lower overall health risk from fish consumption relative to the pre-ban period, high consumption of planktivorous species, especially during warm seasons and in lake regions, may still pose potential health risks. Additionally, MCs likely pose ecological risks to fish populations. These findings provide a crucial baseline for evaluating the long-term effectiveness of the fishing ban and underscore the need for integrated watershed management to safeguard both ecological and public health.